No-tillage shapes a Sinorhizobium-centered rhizosphere network in saline-alkali soybean fields - Zhe Chen; Chuang Ma; Zhiqiang Hu; Zongling He; Jianchao Zhang; Shuyu Li; Lingfang Zhu; Xihui Shen; Baowei Bai (Plant and Soil, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

β-lactam antibiotics vs vancomycin in treating methicillin-sensitive staphylococcus aureus bloodstream infections: a meta-analysis of clinical outcomes - Guoliang Yu; Yonghai Lou; Lingfang He; Zhitao Wang; Yu Ren (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Synergistic copper single sites and nanoparticles nano-trapped in hydrothermally treated Panax pseudo-ginseng for efficient CO2 transformation - Zhichao He; Lingfang Kong; Xuelin Wang; Huiwen Gong; Yunjia Li; Zixuan Lai; Zhonggao Zhou; Kan Li; Guohai Xu; Hongyu Zhen (Journal of Environmental Chemical Engineering, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Development of a new synchronous fluorescence spectrometry combined with Al3+ sensitized for simultaneous and rapid determination of trace flumequine, ciprofloxacin and doxycycline hydrochloride residues in wastewater - Xiaodan Zheng; Menglin Wang; Shiqi Zhang; Zhima Yangcuo; Lifang He; Lingfang Xie; Yurou Ye; Guifen Xu; Zhonghui Chen; Qihong Cai (Water Research, 2024)

Higher ecological risks and lower bioremediation potentials identified for emerging OPEs than legacy PCBs in the Beibu Gulf, China - Li Zhang; Lingfang Ni; Heng Wang; Zhichao Zhang; Yichun Wu; Renming Jia; Junyu He; Zuhao Zhu; Haiyan Jin; Xing Ren; Dongdong Zhang (Environmental Research, 2023)